Human Blood Group Systems and Haemoglobinopathies - Erhabor, Osaro; Munshi, Anjana (IntechOpen, 2021)
The past decade has seen remarkable improvements and advances in the fields of blood transfusion and hematology, particularly with regards to advances in science, technology, method development, quality, standardization, and governance. This book provides more evidenced-based insight into the field of blood transfusion and the management of hemoglobinopathies.